Evaluation of antioxidant activity and acute toxicity of Clausena excavata leaves extract - Albaayit, Shaymaa Fadhel Abbas; Abba, Yusuf; Abdullah, Rasedee; Abdullah, Noorlidah (Hindawi Publishing Corporation, 2014)
Clausena excavata (Lour.), locally known as “Kemantu hitam,” is a common plant in Malaysian folklore medicine. This study evaluated the antioxidant properties of the solvent extracts of C. excavata leaves and determined the acute toxicity of methanolic extract C. excavata (MECE) leaves in Sprague-Dawley rats. Harvested leaves were dried and subjected to solvent extraction using petroleum ether, chloroform, ethyl acetate and methanol in succession. The antioxidant activity of each extract was determined using the ferric-reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picryl dihydrazyl (DPPH) radical scavenging activity. The total phenolic content (TPC) and total flavonoids content (TFC) were estimated by Folin-Ciocalteu and ethanolic aluminium chloride method, respectively. The chloroform extract was found to be highest in flavonoid content, while the methanolic extract showed the highest TPC and antioxidant activity. There was no mortality in rats treated with MECE leaves even at a high dose of 5000 mg/kg body weight. However, the MECE leaves produced mild to moderate pathological changes in the liver and kidneys, shown by mild degenerative changes and leucocyte infiltration. The extract did not affect the haematological parameters or relative weights of the liver or kidneys. Overall, the MECE leaves have potent antioxidant activity and are presumed safe to be used orally as health-promoting product at low to moderate doses.